Deformation and fracture of K3 rotary nickel–titanium endodontic instruments after clinical use. (20th November 2015) - Shen, S. M.; Deng, M.; Wang, P. P.; Chen, X. M.; Zheng, L. W.; Li, H. L.
Abstract: Aim: The aim was to evaluate the incidence and type of defects that occurred with K3 rotary nickel–titanium instruments during routine clinical use. Methodology: A total of 2397 K3 (G‐PACKS, SybronEndo, West Collins, Orange, CA, USA) instruments were collected from a graduate endodontic clinic over 21 months. All the instruments were limited to a maximum use of 30 canal preparations. The collected instruments were measured by a digital caliper to determine whether any fractures had occurred and then were visually inspected for deformation and fracture under a stereomicroscope. The surfaces of fractured instruments were further evaluated under a scanning electron microscope. Data were analysed using chi‐square test and Kruskal–Wallis test. Results: The incidence of instrument defect was 5.63%, consisting of 3.59% fractures and 2.05% deformations. The defect rates of 0.04 and 0.06 files were statistically higher than the other taper groups ( P < 0.003) except for 0.08 files ( P > 0.05). For the fractured instruments, 63.95% failed from flexural fatigue, whilst 36.05% failed from torsion. Conclusion: Flexural fracture was the major mode of fracture for instruments with larger taper. A routine check for instrument integrity particularly for 0.04 and 0.06 files at high magnification is recommended after each clinical use.